Why is optimisation of antimicrobial use difficult at the end of life?. Issue 2 (12th February 2019) - Broom, Jennifer; Broom, Alex; Good, Phillip; Lwin, Zarnie
Abstract: The antibiotic optimisation imperative is now ubiquitous, with national policy frameworks in Organisation for Economic Co‐operation and Development (OECD) countries incorporating the requirement for antimicrobial stewardship within healthcare services. Yet in practice, the optimisation agenda often raises complex ethical‐ and practice‐based dilemmas. Antibiotic use at the end of life is multidimensional. It includes balancing complex issues, such as accuracy of prognostic estimates, benevolence to the individual versus the broader public health, personalised value judgement of time and quality of life and the right to treatment versus the right to die. It also occurs in an emotional context where the clinician and patient (and their family) collectively confront mortality. This provides a scenario where amplification of the already strong social and behavioural forces that drive overuse of antibiotics in many other clinical settings may occur. It therefore offers an important case for illustrating how antibiotic optimisation may be limited by social, value‐based and ethical dilemmas.